EVALUASI PROGRAM GERAKAN 1000 HARI PERTAMA KEHIDUPAN (HPK) DALAM PENCEGAHAN STUNTING DI WILAYAH KERJA PUSKESMAS BANGSRI II KABUPATEN JEPARA - Ratna Wahyuningtias; Intan Zainafree (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
The stunting rate in Jepara Regency continues to change every year. In 2017 there were 16.5% of the 84,717 children under five who were convicted of stunting. In 2018 there was an increase in the percentage to 27%. Public Health in working are of Bangsri II is the area with the highest rating with an incidence rate of 26.44%, was still far from the government's target of reducing the stunting rate to 14% by 2024. Purpose of the research was to determine the evaluation of the 1000 HPK in the work area of the Bangsri II Primary Health Care. The type and design of this research used descriptive qualitative conducted with in-depth interviews. This research informant were 8 people who were selected by purposive sampling technique. Data collection techniques using interviews and observation.The results of this research evaluation of the program’s 1000 HPK indicate that the human aspect is still lacking in human resources for nutrition services. Facilities and infrastructure need to be added and improved so that they are sufficient for program implementation. Aspects of the process for mobilization and implementation there are obstacles in the form of the presence of participants and the lack of awareness of mothers about the importance of weighing toddlers. In the aspect of supervision, control and assessment in the form of recording and reporting has been going well. Routine evaluation is carried out every month in order to improve services. Supervision is carried out periodically every 2-3 times a year by Dinas Kesehatan Kabupaten Jepara. As for the external aspect, there were 3 indicators that have not been achieved due to the COVID-19 pandemic situation accompanied by the implementation of activity restrictions in the community.